Intrinsic happiness: The seed inside each person - Murillo Deglane, María Gracia (2018)
Happiness is a permanent internal state constituted by a genetic predisposition, people’s choices in life, and the way in which people handle the circumstances. Therefore, happiness should be found inside each person and not extrinsically. Extrinsic material goods are only a prerequisite, but not happiness themselves; they are important in order to satisfy basic needs, and start aiming higher.